2012
DOI: 10.1029/2012gl052913
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake recurrence models fail when earthquakes fail to reset the stress field

Abstract: [1] Parkfield's regularly occurring M6 mainshocks, about every 25 years, have over two decades stoked seismologists' hopes to successfully predict an earthquake of significant size. However, with the longest known inter-event time of 38 years, the latest M6 in the series (28 Sep 2004) did not conform to any of the applied forecast models, questioning once more the predictability of earthquakes in general. Our study investigates the spatial pattern of b-values along the Parkfield segment through the seismic cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 23 publications
3
27
0
Order By: Relevance
“…In our view, there is overwhelming evidence that the b value variations are not caused by random artifacts. Our publications on Parkfield, starting with Wiemer and Wyss [] and including formal testing [ Schorlemmer et al ., ] have revealed a near identical spatial pattern of b based on several independent data sets, tested prospectively, and consistently observed for independent time periods [e.g., Tormann et al ., ]. They are also consistent with independent geophysical data, such as geodetic observations that image the asperity/barrier distribution.…”
Section: Artifacts Caused By Under Sampling?supporting
confidence: 86%
“…In our view, there is overwhelming evidence that the b value variations are not caused by random artifacts. Our publications on Parkfield, starting with Wiemer and Wyss [] and including formal testing [ Schorlemmer et al ., ] have revealed a near identical spatial pattern of b based on several independent data sets, tested prospectively, and consistently observed for independent time periods [e.g., Tormann et al ., ]. They are also consistent with independent geophysical data, such as geodetic observations that image the asperity/barrier distribution.…”
Section: Artifacts Caused By Under Sampling?supporting
confidence: 86%
“…The effect is significantly enhanced by offsets of the reservoir layer over the fault zone (Mulders, 2003). Studies indicate that the largest impact on shear stresses on a fault results from differential compaction (Roest & Kuilman, 1994;Mulders, 2003;van den Bogert, 2015). As at a certain time these stresses may act on a larger fault area, seismicity could commence at a comparatively high-magnitude level, as is observed at some fields in the Netherlands (Van Eck et al, 2006).…”
Section: Risk Posed By Induced Seismicitymentioning
confidence: 99%
“…To date, the effect of a mainshock's differential stress change on the subsequent seismicity has not been systematically investigated, but individual case studies suggest that sometimes higher b values are observed after a mainshock (Ogata & Katsura, ; Tamaribuchi et al, ; Tormann et al, , , ; Wiemer et al, ; Wiemer & Katsumata, ). These individual observations highlight the important question of whether such high postmainshock b values are characteristic of aftershock sequences and, if so, whether, when or how they recover.…”
Section: Introductionmentioning
confidence: 99%